Sploty rozkładów jednostajnych - Miszczak, Witold (Convolution of uniform distributions, 2005)
In this paper is given a recursive formula for convolution of k uniform distributions. Besides its novelty, it seems that the proposed formula is very intuitive. It could be useful for the popularization of the convolution method for creating new distributions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 95-108